Aronia melanocarpa Leaves as a Source of Chlorogenic Acids, Anthocyanins, and Sorbitol, and Their Anti-Inflammatory Activity - Agnieszka Zielińska; Dorota Bryk; Katarzyna Paradowska; Iwona Wawer (Polish Journal of Food and Nutrition Sciences)
Aronia melanocarpa E. berries are a valuable component of the healthy diet. They are extremely high in phenolics exhibiting strong antioxidant properties. However, not much information is available on the chemical composition and bioactive potential of chokeberry leaves. Therefore, the analyses of sugars and phenolics of extracts from chokeberry leaves collected from June to October were performed using spectroscopic (NMR) and chromatographic (HPLC-DAD/RI, GC-MS) methods. The leaf extracts contained a significant amount of sorbitol, especially those made of leaves collected since June to July (avg. 145.2 mg/g d.w.). The average contents of Cya-3-Gal and chlorogenic acids in the extracts were at 0.52 mg g d.w. and up to 13.1 mg/g d.w., respectively. Chokeberry leaf extracts from green and red leaves were subjected to the in vitro study on human umbilical vein endothelial cells (HUVCs). Both extracts suppressed TNF-α-induced surface expression of ICAM-1 and VCAM-1 molecules, and exhibited anti-adhesive and anti-inflammatory properties. Green and red leaves may foster a therapeutic potential in the prevention of atherosclerosis and other pathological events involving leucocyte adhesion. That is why chokeberry leaves can be considered as a promising component of functional foods owing to the high content of chlorogenic acids and sorbitol.